Towards an Effective Privacy Impact and Risk Assessment Methodology: Risk Analysis - Alshammari, Majed; Simpson, Andrew (Data Privacy Management, Cryptocurrencies and Blockchain Technology, 2018)
Privacy Impact Assessments (PIAs) play a crucial role in providing privacy protection for data subjects and supporting risk management. From an engineering perspective, the core of a PIA is a risk assessment, which typically follows a step-by-step process of risk identification and risk mitigation. In order for a PIA to be holistic and effective, it needs to be complemented by an appropriate privacy risk model that considers legal, organisational, societal and technical aspects. We propose a data-centric approach for identifying and analysing potential privacy risks in a comprehensive manner.